Effectiveness of hard and soft tsunami countermeasures on loss of life under different population scenarios. (May 2020) - Takabatake, Tomoyuki; Esteban, Miguel; Nistor, Ioan; Shibayama, Tomoya; Nishizaki, Shinsaku
Abstract: The present study proposes a comprehensive investigation of the tsunami-evacuation plans for a popular coastal area considered to be at high risk for tsunami attack. If a coastal region constitutes a renowned sightseeing location or has a popular beach, numerous tourists and beach users could be at risk of a tsunami. However, tsunami risk management strategies have generally been developed considering only local residents, and the effects of the presence of tourist on the effectiveness of countermeasures have rarely been taken into account. To investigate changes in the effectiveness of tsunami countermeasures under different population scenarios, the authors further developed an existing agent-based tsunami evacuation simulation model. Through the application of this model to Yuigahama Beach in Kamakura City, Japan, it was found that the effectiveness of hard measures (i.e., elevating the road embankment) is slightly influenced by the numbers and types of evacuees who are present on or near the beach when a tsunami arrives. However, the effectiveness was greatly influenced by the type of soft measures (i.e., changing the evacuation behaviour) employed. It was also shown that, if there are many evacuees in a coastal area, soft measures merely aiming at early evacuation and guiding evacuees to the closest evacuation place via the shortest route could instead worsen the fatality rate. The present study thus sheds further light on the importance of establishing tsunami mitigation strategies that focus on the tourist population, in order to minimize the number of fatalities that could result from a future event.